HcwA, an Autolysin, Is Required for Heterocyst Maturation in Anabaena sp. Strain PCC 7120 - Zhu, Jinsong (American Society for Microbiology, 2001)
In many filamentous cyanobacteria, vegetative cells can differentiate into heterocysts, cells that are specialized for aerobic fixation of N(2). Synthesis of the heterocyst envelope polysaccharide is dependent on the gene hepA in Anabaena sp. strain PCC 7120. In search of genes that are involved in the regulation of hepA, we transposon mutagenized strain DR1069, which bears a chromosomal hepA::luxAB fusion. One resulting mutant, designated HNL3, grows normally in medium with nitrate and shows poor induction of hepA in response to nitrogen deprivation. In HNL3, transposon Tn5-1058 is inserted within gene hcwA, a constitutively expressed open reading frame whose predicted product resembles N-acetylmuramoyl-l-alanine amidases. Reconstruction of the mutation confirmed that the mutant phenotype resulted from the insertion of the transposon. The induction of hepA in HNL3 is partially restored upon recombination of HNL3 with plasmid-borne, wild-type hcwA. Moreover, HcwA expressed in Escherichia coli exhibits wall-lytic activity. These results suggest that the degradation, or possibly reconstruction, of the cell peptidoglycan layer is a prerequisite for heterocyst maturation.